Copy number analysis of NIPBL in a cohort of 510 patients reveals rare copy number variants and a mosaic deletion. Issue 2 (14th November 2013) - Cheng, Yu‐Wei; Tan, Christopher A.; Minor, Agata; Arndt, Kelly; Wysinger, Latrice; Grange, Dorothy K.; Kozel, Beth A.; Robin, Nathaniel H.; Waggoner, Darrel; Fitzpatrick, Carrie; Das, Soma; Gaudio, Daniela del
Abstract Cornelia de Lange syndrome (CdLS) is a genetically heterogeneous disorder characterized by growth retardation, intellectual disability, upper limb abnormalities, hirsutism, and characteristic facial features. In this study we explored the occurrence of intragenic NIPBL copy number variations (CNVs) in a cohort of 510 NIPBL sequence‐negative patients with suspected CdLS. Copy number analysis was performed by custom exon‐targeted oligonucleotide array‐comparative genomic hybridization and/or MLPA. Whole‐genome SNP array was used to further characterize rearrangements extending beyond the NIPBL gene. We identified NIPBL CNVs in 13 patients (2.5%) including one intragenic duplication and a deletion in mosaic state. Breakpoint sequences in two patients provided further evidence of a microhomology‐mediated replicative mechanism as a potential predominant contributor to CNVs in NIPBL. Patients for whom clinical information was available share classical CdLS features including craniofacial and limb defects. Our experience in studying the frequency of NIBPL CNVs in the largest series of patients to date widens the mutational spectrum of NIPBL and emphasizes the clinical utility of performing NIPBL deletion/duplication analysis in patients with CdLS.